2002
DOI: 10.1053/joca.2002.0811
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic localization of active gelatinases in equine osteochondritis dissecans (OCD) cartilage

Abstract: Sections of articular cartilage from OCD lesions revealed MMP activity, especially in the deep zone adjacent to the calcified subchondral bone. This MMP activity could account for the loss of cartilage integrity in the deep cartilage zone and the vertical lines of activity could represent areas of mechanical weakness, likely to result in fissures and the release of cartilage fragments into the joint space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…41 We examined the gene expression levels of gelatinases and their endogenous inhibitors, the TIMPs. In co-cultured chondrocytes, we found that IL-1β-regulated MMPs and TIMPs at the transcriptional level (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…41 We examined the gene expression levels of gelatinases and their endogenous inhibitors, the TIMPs. In co-cultured chondrocytes, we found that IL-1β-regulated MMPs and TIMPs at the transcriptional level (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 (also known as gelatinase A) can degrade type IV collagen of basement membranes, collagen types V, VII, and X, as well as denatured collagen (gelatin), fibronectin, laminin, elastin, and proteoglygans [52]. MMP-2 activity also is increased in joint disease in the horse, [38,53] and dog [54]. Furthermore, MMP-2 activation has been identified in a variety of joint diseases [55].…”
Section: Discussionmentioning
confidence: 99%
“…In the arthritides (including OA and rheumatoid arthritis [RA]), this balance is disrupted, leading to a net loss of articular cartilage. Evidence of altered proteinase activity also has been identified in OC tissue [38][39][40].…”
Section: Introductionmentioning
confidence: 89%
“…In recent years, many investigators have focused their research on the biochemical events involved in the pathogenesis of joint diseases, but few studies have addressed the aetiology of OCD. Some authors have reported an increase in the catabolic activity of chondrocytes with enzymatic degradation of the extracellular matrix due to the action of metalloproteinases, 5 but further studies aimed at elucidating the mechanisms involved are needed. Apoptosis has been identified as one of the mechanisms associated with different processes observed in osteoarthritis (OA) and rheumatoid arthritis 6 .…”
mentioning
confidence: 99%